2019
DOI: 10.1021/acsami.9b17858
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Increasing the Rate of Defect Annihilation in the Directed Self-Assembly of High-χ Block Copolymers

Abstract: Directed self-assembly (DSA) of high-χ block copolymer thin films is a promising approach for nanofabrication of features with length scale below 10 nm. Recent work has highlighted that kinetics are of crucial importance in determining whether a block copolymer film can self-assemble into a defect-free ordered state. In this work, different strategies for improving the rate of defect annihilation in the DSA of a silicon-containing, high-χ block copolymer film were explored. Chemo-epitaxial DSA of poly­(4-metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…29 Moreover, measuring the correlation length of unguided self-assembled BCP thin films, Ellison et al demonstrated that it is possible to directly predict the density of kinetically trapped defects in BCP thin films deposited on a fixed chemical pattern and self-assembled under the same process conditions. 31 Therefore, the understanding of the selfassembling process for a BCP deposited on an unpatterned substrate is fundamental for the development of any directed self-assembly based nanolithograpic application. 25,26,31…”
Section: Overall Viewmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Moreover, measuring the correlation length of unguided self-assembled BCP thin films, Ellison et al demonstrated that it is possible to directly predict the density of kinetically trapped defects in BCP thin films deposited on a fixed chemical pattern and self-assembled under the same process conditions. 31 Therefore, the understanding of the selfassembling process for a BCP deposited on an unpatterned substrate is fundamental for the development of any directed self-assembly based nanolithograpic application. 25,26,31…”
Section: Overall Viewmentioning
confidence: 99%
“…31 Therefore, the understanding of the selfassembling process for a BCP deposited on an unpatterned substrate is fundamental for the development of any directed self-assembly based nanolithograpic application. 25,26,31…”
Section: Overall Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent research on DSA has also been greatly focused on the study, understanding and mitigation of defects [ 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Minimization of defects is crucial for the incorporation of DSA into high-volume manufacturing, either as a primary patterning option or in combination with already established techniques like DUV or EUV.…”
Section: Principles Of the Dsa Of Block Copolymersmentioning
confidence: 99%
“…The self-assembly of a monolayer of a given BCP on a flat, featureless surface results in a polycrystalline morphology with uncorrelated nano- to micron-sized domains, with a significant concentration of defects . The ITRS (now IDRS roadmap) has specified a target of a maximum defectivity of ∼1 per 100 cm –2 , which is several orders of magnitude lower than that quantified in patterns derived from these monolayers of self-assembled BCPs on substrates lacking guiding patterns. Some kinetically trapped nonequilibrium metastable configurations in the free energy landscape persist even through long annealing times, which is an issue for high volume manufacturing on 300 mm wafers. ,,, In an attempt to minimize defect formation during the course of self-assembly, much effort has been directed toward the optimization of annealing of the spin-coated BCP films, including solvent vapor, thermal (including microwave irradiation), a combination of solvent and thermal (solvothermal), , laser annealing, , shear flow, , and annealing within an electric field .…”
Section: Introductionmentioning
confidence: 99%